Dual axis solar angle tracking system without any sensor - Er, Zuhal; Balcı, Elif (Journal of Energy Systems, 2018)
Owing to swift and irrepressible increase in globalization, the power requirement and energy utilization are also increasing day by day. To compensate the power needs, various renewable energy sources which consist solar energy systems are been used in order to satisfy this ample demand. In order to eliminate the efficiency limits of photo-voltaic panel in a solar energy system, there are several methods by solar tracking. In this study, a dual axis solar tracker system is newly designed and tested at several times to track the sun position. A new approach to solar panel systems has been investigated and designed in this study via motivation of no sensor and less mechanical construction. Since a fixed solar panel will not work with the highest solar radiation at every moment of a day; a mobile system which has solar tracker can consider that it will work more efficiently. Owing to the restricted solar radiation reception of fixed panel systems for, a new fabricate-more efficient solar panel has been designed. Photo-voltaic tracking mechanism having two axes has been constructed and fabricated. The parts of the system have selected carefully via the multi decision criteria and boundary conditions of the system has settled by calculating solar angles. This paper presents the mentioned design construction detail and -however there is no any sensor- working results of the tracker whereby the movement of a PV panel was controlled to setting of programming of a programmable logic-controller (PLC). To perform the technical task, all electronic circuits and necessary software have been designed and developed with some opportunities in industry and Istanbul Technical University. Fabricated this new design tracker works very well and it is tested with several experimental studies. The results of the experimental studies represent best performance of the fabricated new design. Due to results, sensibility for vertical axis movement of the system is stated 1 degree via calculation. Based on the obtained results this study can conclude that the fabricated new design for a solar dual axis tracking system offers several advantages concerning the improvement of efficiency.
Keywords: Solar tracking; Dual axis tracking; Solar panel; PLC; Solar calculations